Perirhinal cortical contributions to object perception. - Buckley, M; Gaffan, D (2006)
The traditional theory of the medial temporal lobe (MTL) memory system asserts that the primate MTL (hippocampus, perirhinal, entorhinal and parahippocampal cortices) is exclusively involved in consolidating declarative memories. However, several recent reports have directly challenged this dogma by arguing that MTL structures also contribute to perception. Controversy remains as many of the behavioural tasks used have confounded memory with perception. We review the evidence here and highlight new studies in humans and macaques that indicate a perceptual role for MTL in the absence of such confounds. We argue that the challenge to MTL memory system theory is substantiated and that the implications are considerable, namely that most psychologists and neuroscientists have held a fundamentally flawed view of how memory is implemented in the brain.